Türkiye'nin Eğitim, Sağlık ve İktisadi Göstergeleri Arasındaki Etkileşiminin Kanonik Korelasyon Analizi ile İncelenmesi - (:unkn) unknown (My University, 2005)
Bir ülkenin gelişmişlik düzeyini belirleyen en önemli unsur, o ülkenin ekonomik durumudur. Yaklaşık 20 yıl öncesinden itibaren sadece ekonomik göstergelerin yeterli olmadığı ve ekonomik büyümenin sosyal gelişmeyi de beraberinde getirmesi gerektiği belirlenmiştir. Bir ülkenin gelişmişlik düzeyini ekonomik faktörlerin yanı sıra insani faktörler de belirlemektedir. Bu sebeple çeşitli kurumlarca farklı indeksler geliştirilmiş; ekonomik göstergelerin yanısıra eğitim ve sağlık göstergeleri de eşit ağırlıkla bu indekslere dahil edilmiştir. Bu çalışmanın amacı 2000 Genel Nüfus Tespiti sonuçlarını kullanarak Türkiye için ekonomik göstergeler ile sosyal göstergeler arasındaki etkileşimin detaylı bir şekilde analiz edilmesidir. Amaç doğrultusunda çok değişkenli istatistiksel analiz tekniklerinden Kanonik Korelasyon Analizi kullanılmıştır.

The most important factor that determines the development level of a country is its economic situation. Since nearly 20 years, it became clear that not only economic indicators were sufficient and economic development has to be realized along with social development. Not only economic factors but also human factors determine the economic development of a country. Different indices have been developed by various institutions. Educational and Health indicators along with economic ones were equally included in these indices. The aim of this study is to analyze in detail the interaction between the social and economic indicators for Turkey by using the results of 2000 Census. To get the results Canonical Correlation Analysis, which is one of the multiple variant statistical analysis techniques, was used. As a result of this study, it is found that there is a significant relation between economic and social developments; whereas, the interaction between economic and educational indicators was found higher when compared to the interaction between economic and health indicators.
Keywords: İş; İşletme Finans; İktisat; Coğrafya; İşletme; Siyasi Bilimler; Kamu Yönetimi; Sosyal Çalışma; Sosyoloji